Implementing Open Science policies into library processes – case study of the University of Eastern Finland library - Saarti, Jarmo; Rosti, Tomi; Silvennoinen-Kuikka, Helena (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
This is a case study about the creation of open science services in the University of Eastern Finland. The library has overseen the open science services that have been actively implemented from 2010 onwards due to the development of the digitalisation of science and open science policies. A survey was conducted to determine how the UEF’s academic faculty use the services provided as well as their attitudes towards opening their own research findings in this manner. The researchers seem to be most interested in issues that influence their daily work, i.e. data management plans and opening their publications. It seems that the culture of openness is still at the development stage within UEF. The innovators, i.e. active research groups and researchers, are already practicing and encouraging openness, but the majority of the academic staff seems to be either unaware of open science or unwilling to implement it, due to the fact that incentives and career advancements still support the traditional way of conducting research.